Medicinal plants used for reproductive health by women in Jaro, Leyte - Robel, Jo Queenstein L. (Jo Queenstein L. Robel, 2014)
The study investigated the local medicinal plants used by women in Jaro, Leyte for the treatment of their reproductive health problems. The parts of the plant used, the methods of preparation, and the route of administration were also identified. There were 101 respondents in the survey which included local women who use medicinal plants, Barangay Health Workers, and the trained "hilots" who practice midwifery. Data were gathered using a semi-structured questionnaire. The interview was done in Waray, the dialect used in Jaro, Leyte. The plants were collected from their sources, pressed, dried, poisoned, and then mounted for identification and verification purposes. There were 31 medicinal plant species identified by the respondents that are used to treat reproductive-related problems of women in the town. The plants belong to family Acanthaceae, Annonaceae, Araceae, Bixaceae, Compositae, Crassulaceae, Euphorbiacaeae, Lamiaceae, Lauraceae, Malvaceae, Moringaceae, Myrtaceae, Pandanaceae, Piperaceae, Poaceae, Rutaceae, Verbenaceae, and Zingiberacae, with the highest number of species (13%) belonging to family Lamiaceae. There were 21 reproductive health problems identified which are associated with menstruation, pregnancy, labor, after delivery, and abortion. Leaves (62.47%) were the most used plant part in medicinal treatments, while the stem (0.23%) was the least used part. Heating, boiling, decoction, and soaking were the methods employed in the herbal preparations, which were administered either externally or internally.